1982
DOI: 10.1002/ccd.1810080203
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between left ventricular functional response to isometric exercise and asynergic contraction and diastolic stiffness

Abstract: Either augmentation or impairment of left ventricular function has previously been reported in different patients, in response to isometric exercise. To identify the mechanisms associated with these disparate responses, the effects of submaximal sustained handgrip upon left ventricular systolic and diastolic properties were studied in 29 patients during diagnostic catheterization. In 16 patients (group I), ejection fraction, mean Vcf, and the mean systolic ejection rate remained constant, while the ratio of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Two previous studies (Miyazawa et al 1980;Ludbrook et al 1982) have demonstrated that the responses to increased afterload produced by isometric exercise differ between normal subjects and patients with heart disease. In these studies, the LVEF increased in normal subjects but decreased in patients with heart disease in response to increased afterload.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies (Miyazawa et al 1980;Ludbrook et al 1982) have demonstrated that the responses to increased afterload produced by isometric exercise differ between normal subjects and patients with heart disease. In these studies, the LVEF increased in normal subjects but decreased in patients with heart disease in response to increased afterload.…”
Section: Discussionmentioning
confidence: 99%